"At heart, I am a village person": An interview with Bhalchandra Nemade. Issue 1 (4th March 2017) - Nerlekar, Anjali
Abstract: Bhalchandra Nemade is the author of six novels, ranging from Kosla (1963) to Hindu (2010). He has also published two collections of poetry and several substantial books of criticism. He occupied a significant place in Bombay literary life in the 1960s and is at the center of the Marathi canon today. In this interview, conducted in Dahisar, Mumbai in 2011 and continued in 2015 in Santa Cruz, Mumbai, Nemade discusses his studies in Pune, and his early encounters with the Marathi tradition, his arrival in Bombay and involvement with the journal Rahasyaranjan . He recounts his move to Aurangabad and his part in establishing the little magazine Vacha, and his connections and collaborations with other writers in the intellectual and artistic milieu of the 1960s and after. Nemade also reflects on his defence of nativism or deshivad, and his misgivings about the place of English in Indian education.